Effect of Pneumothorac Duration on Oxidative Stress Level of Wistar Rat’s Lung - Faisal Mutaqien; Bermansyah; Irsan Saleh (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2019)
Abstract Introduction. Extensive pneumothorax with a long duration of symptoms can be dangerous. Broad pneumothorax can cause hypoxemia which can cause increased production of free radicals in the lung tissue (pulmonary oxidative stress). Oxidative stress in the lungs can indicate the degree of damage or disruption of cells in the lungs due to hypoxia. Methods. There were 4 groups each consisting of 6 mice: 24-hour pneumothoric group (A), 48-hour pneumothoric (B), 72-hour pneumothoric (C) and control (D). Pneumothorac is made by air injection into the right chest pleural cavity, then on an X-ray. All samples were examined for PaO2 to ascertain their level of hypotension. After that, the rats were examined for their lungs malondialdehyde (MDA) levels to find out their stress oxidation stress levels. Results. All groups of pneumothorac mice experienced hypoxemia. The average MDA level was higher in the pneumothorac group, but it was statistically significant only in the 72 hour (C) group with p = 0.031. MDA levels in each group were 1.601 ± 0.739 (A), 1.585 ± 0.714 (B), 2.256 ± 0.513 (C), 1.243 ± 0.162 (D). Conclusion. Pneumothorax can cause pulmonary oxidative stress if the pneumothorac is large in volume and the duration of symptoms reaches 72 hours. MDA can be a marker of cell disruption or injury in cases of pneumothorax who have experienced hypoxemia.